Essential role of Wnt5a‐Ror1/Ror2 signaling in metanephric mesenchyme and ureteric bud formation. (3rd February 2016) - Qi, Xiaoyuan; Okinaka, Yuka; Nishita, Michiru; Minami, Yasuhiro
Abstract : Spatiotemporally regulated interaction between the metanephric mesenchyme (MM) and Wolffian duct (WD) is essential for the induction of a single ureteric bud (UB). The MM then interacts with the tip of the UB to induce outgrowth and branching of the UB, which in turn promotes growth of the adjacent MM. The Ror family receptor tyrosine kinases, Ror1 and Ror2, have been shown to act as receptors for Wnt5a to mediate noncanonical Wnt signaling. Previous studies have shown that Ror2‐ mutant mice exhibit ectopic formation of the UB, due to abnormal juxtaposition of the MM to the WD. We show here that both Ror1 and Ror2 are expressed in the mesenchyme between the MM and WD during UB formation. Although Ror1 ‐mutant mice show no apparent defects in UB formation, Ror1;Ror2 ‐double‐mutant mice exhibit either defects in UB outgrowth and branching morphogenesis, associated with the loss of the MM from the UB domain, or ectopic formation of the UB. We also show genetic interactions between Ror1 and Wnt5a during UB formation. These findings suggest that Wnt5a‐Ror1/Ror2 signaling regulates cooperatively the formation of the MM at the proper position to ensure normal development of the UB. Abstract : Spatiotemporally regulated interaction between the metanephric mesenchyme (MM) and Wolffian duct (WD) is essential for inducing a single ureteric bud (UB). We found that Ror1;Ror2‐double‐mutant mice exhibit defects in UB formation, associated with the loss of the MM at the UB domain. Our findings suggest that Wnt5a‐Ror1/Ror2 signaling regulates cooperatively the formation of the MM at the proper position to ensure normal development of the UB.